Non Hodgkin T cell lymphoma: an atypical clinical presentation - Maio, Paula (Sociedade Brasileira de Dermatologia, 2013)
Cytotoxic lymphomas comprise a spectrum of peripheral T-cell lymphomas that can have a initial or late cutaneous presentation. We describe a 46-year-old man from Cape Verde, with a dermatosis involving his face and trunk, consisting of monomorphic papules with a smooth surface and both motor and sensory polyneuropathy.The hypothesis of leprosy was supported by the clinical and initial hystopathological findings and the patient was referred to our hospital with suspected Hansen's disease. In the new skin and lymph node biopsies a lymphocyte population was identified whose immunohystochemistry study allowed the diagnosis of T-cell lymphoma with expression of cytotoxic markers. The patient was started on chemotherapy with initial remission of the skin lesions but, subsequently, progression of systemic disease.